Mapping Mindful Consumption Through a Spiritual Lens: A Bibliometrics - Imam Yanuar; Setyanto, Refius Pradipta Setyanto (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2026)
In recent years, the intersection of spirituality and mindful consumption has garnered growing academic interest as scholars seek to understand the internal value systems that guide ethical and sustainable consumer behavior. This study presents the first bibliometric analysis of literature explicitly linking spirituality with mindful consumption, drawing on 37 peer-reviewed articles published between January 2010 and April 2025 in the Scopus database. Guided by PRISMA protocols, the analysis employed Bibliometrix (R-package) and VOSviewer to explore the intellectual, conceptual, and social structures of the field. Descriptive analysis revealed a gradual increase in scholarly output, with research spanning multiple disciplines including marketing, psychology, and sustainability studies. Thematic mapping identified core clusters centered on moral norm activation, spiritual values, empathy, minimalism, and identity-based consumption. Conceptual structure analysis and keyword co-occurrence maps indicated that spirituality is primarily positioned as an antecedent and, to a lesser extent, as a moderator of mindful consumption. However, the roles of spirituality as a mediator or as an outcome remain significantly underexplored. This paper concludes with a call for future research to test dynamic, multidirectional models of spirituality in consumer behavior, examine longitudinal effects, and deepen cultural-contextual understanding of spiritually motivated consumption.